Pengaruh Islam terhadap Perkembangan Budaya Jawa: Tembang Macapat - Asmaun Sahlan; Mulyono Mulyono (UIN Maulana Malik Ibrahim Malang, 2012)
Islam came to Indonesia since the seventh century AD has a major influence on the transformation of the local culture. From cultures that were previously heavily influenced by Hinduism is primarily based on two major books from India, the Ramayana and the Mahabharata to the new culture that is influenced by Islamic values. One form of cultural transformation in the field of Javanese literature is the birth of the tembang macapat (song of macapat). Tembang macapat is a form of transformation from Javanese literature of the form kakawin literary dan kidung (ancient Javanese song) became a form of Java new song (gending). During its development, macapat song contains a lot of Islamic values so utilized by teachers, preachers, religious scholars and Ulama’ to the means of education and transformation of Islamic values. Islam datang ke Indonesia sejak abad ke tujuh Masehi memiliki pengaruh besar terhadap transformasi budaya setempat. Dari kebudayaan yang sebelumnya banyak dipengaruhi oleh agama Hindu terutama didasarkan pada dua karya besar dari India yaitu Ramayana dan Mahabharata menuju kepada kebudayaan baru yang dipengaruhi oleh nilai-nilai Islam. Salah satu bentuk transformasi kebudayaan dalam bidang sastra Jawa adalah lahirnya tembang macapat. Tembang macapat merupakan bentuk transformasi sastra Jawa dari bentuk kakawin dan kidung menjadi sastra puisi yang berupa lagu/gending. Dalam perkembangannya, tembang macapat banyak mengandung nilai-nilai Islam sehingga dimanfaatkan oleh para guru, mubaligh, kyai maupun ulama’ untuk sarana pendidikan dan dakwah nilai-nilai Islam.